Performing in Groups - Jane Beethoven; Rosanne Emery (Music magic video library, 1991)
Viewers see and hear performers from different parts of the world - - Discover the combined tone colors of a wide variety of instruments - - Enjoy performances in many different styles - - Understand what the individual players contributes to a group.